1972
DOI: 10.1002/mrc.1270040509
|View full text |Cite
|
Sign up to set email alerts
|

(Pentafluorophenyl)sulfur fluorides, 19F NMR

Abstract: The low-temperature 19F NMR spectra of (pentafluoropheny1)sulfur trifluoride are explained by the trigonal bipyramid structure (la) with the pentafluorophenyl ring in the basal plane and a relatively high barrier to rotation about the C-S bond. In the presence of a hydrogen fluoride scavenger, there is a high barrier to intramolecular rearrangement of the sulfur fluorines about the sulfur atom. The single basal fluorine couples strongly with one ortho fluorine and weakly with the other, but the two apical fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…anism involving the development of negative charge on sulfur in a transition state resembling 16. Known analogues of 16 include the SF5species reported by Christe33a and Muetterties.33b Vibrational studies333 of SF5-indicate it to possess Cnv symmetry. Similar sulfur anions have been suggested in NMR ligand exchange studies.34, 35 Archie and Westheimer36 have reported kinetic evidence indicating an associative mechanism for the basic hydrolysis of pentaaryloxyphosphoranes involving hexacoordinated phosphorus. Hexacoordinate phosphorus compounds are well known.37,38 Ramirez38 and Schmutzler39 have shown that pentaalkoxyphosphoranes readily add pyridine or trimethylphosphine to give stable adducts of this type.…”
Section: (Xsupporting
confidence: 56%
See 1 more Smart Citation
“…anism involving the development of negative charge on sulfur in a transition state resembling 16. Known analogues of 16 include the SF5species reported by Christe33a and Muetterties.33b Vibrational studies333 of SF5-indicate it to possess Cnv symmetry. Similar sulfur anions have been suggested in NMR ligand exchange studies.34, 35 Archie and Westheimer36 have reported kinetic evidence indicating an associative mechanism for the basic hydrolysis of pentaaryloxyphosphoranes involving hexacoordinated phosphorus. Hexacoordinate phosphorus compounds are well known.37,38 Ramirez38 and Schmutzler39 have shown that pentaalkoxyphosphoranes readily add pyridine or trimethylphosphine to give stable adducts of this type.…”
Section: (Xsupporting
confidence: 56%
“…Acetyl chloride (2 ml, excess) was added to the mixture, which became homogeneous after 10 min. The solvent and excess acetyl chloride were removed in vacuo to give 1.03 g (99%) of 14: mp 165-167 °C (sealed tube); NMR (CDC13) 2.35 (s, 3, CH3), 2.68 (s, 3, CH3), 7.28 (m, 4, tolyl aromatic CH), 7.60 (broad s, 1, H ortho to fluoroalkyl group), 7.73 (d, 1, J = 9.0 Hz, H meta to S in the fused ring), 9.14 (d, 1, J = 9.0 Hz, ortho to S in the fused ring); 19F NMR (CDC13) 74.6 (q, 3, / = 9.4 Hz), 76.4 (q, 3, J = 9.4 Hz); IR (CHC13) 3000 (w), 1250 (s, 4 strong peaks), 1110 (m), 970 (m), 790 cm-1 (m); mass spectrum (70 eV) m/e (rel intensity (414 (0.98, M-+ for 35C1), 416 (0.28, M-+ for 37C1), 380 (45, •+ -Cl), 379 (94, M-+ -HC1), 345 (1.7, M-+ -CF3), 241 (100), 219 (83), 197 (35). Anal.…”
Section: Methodsmentioning
confidence: 99%
“…12 In a 10 ml plastic vessel equipped with a stir bar, bis-(pentafluorophenyl) disulfide (1.7 g, 4.29 mmol) was dissolved in 1,1,2-trichlorotrifluoroethane. 12 In a 10 ml plastic vessel equipped with a stir bar, bis-(pentafluorophenyl) disulfide (1.7 g, 4.29 mmol) was dissolved in 1,1,2-trichlorotrifluoroethane.…”
Section: Pentafluorophenylsulfur Trifluoride (C 6 F 5 Sf 3 )mentioning
confidence: 99%
“…Systems such as phenyl-substituted phosphonitrilic fluoride trimers (1879) fluorosilyl amines (1880), substituent effects on silicon of fluorophenylsilanes, (1881), (pentafluorophenyl)sulfur fluorides (1882), substituted fluorothiophenes (1883), imidosulfuryl fluorides (1884), and fluorine exchange in diorganoselenium difluorides (1885) have been studied by 19F NMR. Spectra for the trifluoroxenon(IV) M-fluorobispentafluorantimonate(V) cation ( 1886) and complexes of antimony and bismuth trifluorides with strong fluoride acceptors (1887) have also been described.…”
Section: Fluorinementioning
confidence: 99%